The Influence of Free Trial Experience and Aesthetic Design on Buying Interest Genshin Impact Game Products - Yusof, Yusrin Bin; Supriyanto, Antok; Wibowo, Januar (GREENOMIKA, 2023)
The research was carried out with the aim of analyzing the influence of free trial experience and aesthetic design on buying interest Genshin Impact game products in Surabaya. A quantitative approach is used to answer the research problem formulation. The research sample consisted of 95 respondents who used the Genshin game in Surabaya. The data analysis technique is carried out using partial least square analysis using the SmartPLs program. The research results show that free trial experience and aesthetic design have a significant positive effect on interest in purchasing Genshin game products in Surabaya.